Show that (4pq+3q^2) – (4pq-3q^2) =48pq^2

Question

Show that (4pq+3q^2) – (4pq-3q^2) =48pq^2

in progress 0
Sophia 2 weeks 2021-09-04T17:51:45+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-04T17:53:20+00:00

    Step-by-step explanation:

    (4pq+3q)^2 −(4pq−3q)^2 =48pq^2

    LHS=(4pq)^2 +2 (4pq)(3q)+ (3q)^2 −[(4pq) −2(4pq)(3q)+(3q)^2]

    =16p^2 q^2 +24pq^2 +9q^2- 16p^2q^2+24q ^2 −9q^2

    =48pq^2

    =RHS

    therefore LHS=RHS

    if u hope my answer is helpful plz mark me as brainlist.

    tq.................

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )